2021
DOI: 10.1136/archdischild-2020-320241
|View full text |Cite
|
Sign up to set email alerts
|

Hypotension in Preterm Infants (HIP) randomised trial

Abstract: ObjectiveTo determine whether restricting the use of inotrope after diagnosis of low blood pressure (BP) in the first 72 hours of life affects survival without significant brain injury at 36 weeks of postmenstrual age (PMA) in infants born before 28 weeks of gestation.DesignDouble-blind, placebo-controlled randomised trial. Caregivers were masked to group assignment.Setting10 sites across Europe and Canada.ParticipantsInfants born before 28 weeks of gestation were eligible if they had an invasive mean BP less … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(33 citation statements)
references
References 30 publications
1
28
0
Order By: Relevance
“…Some reasons include direct effects of illness, medications, immaturity, and nonhomogeneity across premature infants within the same GA. 14 Recommendations (1992) from the Joint Working Party of British Association of Perinatal Medicine were to maintain MAP greater than the infants' GA in a millimeter of mercury. 15 The hypotension in preterm infants 16 study showed no outcome differences (while lacking power) between infants treated with dopamine or placebo with a blood pressure goal of over GA. 14 Other work showed GA as an adequate MAP threshold. 15,17 Original studies suggested that MAP goals under 30 mm Hg may lead to an increased risk of IVH.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Some reasons include direct effects of illness, medications, immaturity, and nonhomogeneity across premature infants within the same GA. 14 Recommendations (1992) from the Joint Working Party of British Association of Perinatal Medicine were to maintain MAP greater than the infants' GA in a millimeter of mercury. 15 The hypotension in preterm infants 16 study showed no outcome differences (while lacking power) between infants treated with dopamine or placebo with a blood pressure goal of over GA. 14 Other work showed GA as an adequate MAP threshold. 15,17 Original studies suggested that MAP goals under 30 mm Hg may lead to an increased risk of IVH.…”
Section: Discussionmentioning
confidence: 96%
“…The "Avoiding Hypotension in Preterm Neonates" trial published by Drs. Thewissen et al investigated cNIRS values in neonates and developed prescribed interventions based on recorded instabilities 22,23 . The study showed treatment of hypotension with dopamine in extremely preterm infants increases mean arterial blood pressure but does not improve cNIRS values.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Hypotension treatment is a clinical challenge in VLBW infants, and optimal blood pressure ranges are debated [ 39 ]. Considering that infants with normal blood pressure often receive inotropes [ 40 ], restricting inotropes when treating premature infants could be beneficial [ 41 ]. However, it is worth noting that infants with hypotension have worse outcomes than infants with normal blood pressure [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…Ways to increase blood pressure have been widely studied in controlled trials. The clinical benefits, however, has mainly been studied using epidemiological methods, and only very recently a randomized, but unfortunately very underpowered, clinical trial was completed (23). As far as we know, little in this direction is underway for electric cadiometry.…”
Section: Benefits Harms and Costsmentioning
confidence: 99%